PENGGUNAAN MEDIA INTERACTY PADA HASIL BELAJAR SISWA DIKELAS 4 UPT SD NEGERI 238 GRESIK - Isrofiana, Zalsabillah; Eka Tiyas Rifayanti, Zuni (Prodi Pendidikan Guru Sekolah Dasar, 2025)
Learning media is a tool used in the learning process to convey information to students with the hope that using learning media the learning process will run more systematically and can also solve problems in the learning process. The use of learning media that is still lacking is one of the factors that makes student learning outcomes less. This researcher aims to describe the use of interactive media find a partner on the learning outcomes of grade 4 students in Pancasila learning at UPT SD Negeri 238 Gresik. This method uses qualitative research, with the instrument that the way to use interactive media is to find questions by looking for the same images. Teacher activities in using this media starting from the opening, core and closing activities also run optimally and by using this interactive media, student learning outcomes increase by 90%.